2017
DOI: 10.1111/sode.12264
|View full text |Cite
|
Sign up to set email alerts
|

Thinking for themselves? The effect of informant independence on children's endorsement of testimony from a consensus

Abstract: Testimony agreement across a number of people can be a reassuring sign of a claim's reliability. However, reliability may be undermined if informants do not respond independently. In this case, social consensus may be a result of indiscriminate copying or conformity and does not necessarily reflect shared knowledge or opinion. We examined children's emerging sensitivity to consensus independence by testing whether it affected their judgements in a social learning context. Children ages 5, 6, and 8-9 years (N 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 53 publications
5
14
0
Order By: Relevance
“…More recent work has investigated how and under what conditions children are susceptible to consensus (Burdett et al, 2016; Hu, Buchsbaum, Griffiths, & Xu, 2013; Hu, Whalen, Buchsbaum, Griffiths, & Xu, 2015). Yet little work has examined sensitivity to the quality of consensus, even though this seems directly relevant to a wide range of psychological and sociological questions (but see Einav, 2014, 2018). Consensus is critical not only as we decide which rumors to take seriously but also as we interpret academic articles, news sources, and virtually any kind of information for which there can be a consensus at all.…”
Section: The Consequences Of Consensusmentioning
confidence: 99%
“…More recent work has investigated how and under what conditions children are susceptible to consensus (Burdett et al, 2016; Hu, Buchsbaum, Griffiths, & Xu, 2013; Hu, Whalen, Buchsbaum, Griffiths, & Xu, 2015). Yet little work has examined sensitivity to the quality of consensus, even though this seems directly relevant to a wide range of psychological and sociological questions (but see Einav, 2014, 2018). Consensus is critical not only as we decide which rumors to take seriously but also as we interpret academic articles, news sources, and virtually any kind of information for which there can be a consensus at all.…”
Section: The Consequences Of Consensusmentioning
confidence: 99%
“…Although some social characteristics could be perceived as having both epistemic and social components (i.e., having a native or non‐native accent; Corriveau, Kinzler, & Harris, ; having in‐group or out‐group status; Elashi & Mills, ; belonging to a consensus or dissenting; Corriveau, Fusaro, & Harris, ; Schillaci & Kelemen, ), we classified these studies in the social characteristics category. We did this based on evidence that children make social judgments using these characteristics (e.g., children were more likely to make friends with kids who share the similar accent with them; Souza, Byers‐Heinlein, & Poulin‐Dubois, ) and that the social element of behaviors such as belonging to a consensus is likely to be more salient to 3‐ to 6‐year‐old children than the epistemic element (Einav, ). For inclusion in the third meta‐analysis (interaction of characteristics), children had to be presented with two informants who simultaneously differed along epistemic and social characteristics, where one informant was more knowledgeable but had negative social characteristics, whereas the other informant was less knowledgeable but had positive social characteristics (e.g., accurate/unfamiliar‐inaccurate/familiar; e.g., Corriveau & Harris, ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings point to a developmental shift toward a preference for more abstract knowledge, as children strengthen their reasoning capacities and ability to adapt to their learning environment. In a similar way, a recent study by Einav () has demonstrated that in receiving conflicting testimony about an unfamiliar country from two consensual groups of informants, 8‐ and 9‐year‐olds favor the claims of the independent group (who respond privately), while 5‐year‐olds prefer to accept the claims of the non‐independent group (who has access to each other's answers). As older children value the independence of group consensus over conformity to group opinions and, therefore, ensure a greater reliability of consensual decisions, they tend to increase their adaptive fit with respect to solving complex cognitive tasks posed by their environment.…”
Section: Discussionmentioning
confidence: 84%